MANAJEMEN ORGANISASI KAMPUS DI ERA PANDEMI COVID-19 (Studi pada UKK KSR-PMI Unit IAIN Pekalongan) - Hendri Hermawan; Diah Ayu Safitri; Dina Nur Amilah Balbisi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
Management is a way of managing an organization or institution. Management makes an organization achieve its goals and vision and mission. Proper management will make the organization run well and according to plan. However, the Covid-19 pandemic has caused changes in various social, economic, educational and health arrangements. Other things also have an impact on organizational management as well as campus organizations. All planned activities must be replaced and converted to online activities or with certain restrictions and permits. Seeing this, it is necessary to have new management in accordance with the Covid-19 pandemic era on campus so that the organization can run. This research was conducted using qualitative methods. It is hoped that with the existence of organizational management on campus during the Covid-19 Pandemic, the activities carried out can still run well even though during the Covid-19 pandemic. Organizational management in studies at UKK KSR-PMI IAIN Pekalongan such as organizational management planning during the pandemic, management, implementation and supervision in running the organization in accordance with the Covid-19 pandemic era.